Prognostic impact of trisomy 21 in follicular lymphoma. (12th November 2018) - Mitsui, Takeki; Yokohama, Akihiko; Koiso, Hiromi; Saito, Akio; Toyama, Kohtaro; Shimizu, Hiroaki; Ishizaki, Takuma; Irisawa, Hiroyuki; Takizawa, Makiko; Saitoh, Takayuki; Murayama, Kayoko; Matsumoto, Morio; et al.
Summary: The chromosomal abnormalities associated with follicular lymphoma (FL) prognosis are not fully elucidated. Here, we evaluated the pattern of chromosomal abnormalities in FL, and clarified the correlations between the cytogenetic features and clinical outcome. Cytogenetic analysis was performed using standard methods of Giemsa‐banding at diagnosis for 201 FL patients admitted to our hospitals between 2001 and 2013. The identified chromosomal abnormalities were: t(14;18)(q32;q21) (59·2%), +X (17·9%), del(6)(q)/‐6 (16·9%), +7 (14·4%), abnormality of 1q12‐21/1q (12·9%), del(13)(q)/‐13 (11·9%), abnormality of 3q27 (10·4%), abnormality of 10q22‐24 (10·0%), +12/dup(12)(q) (10·0%), abnormality of 1p21‐22/1p (9·0%), +18 (9·0%), del(17)(p)/‐17 (5·0%), and a complex karyotype (54·7%). Patients with trisomy 21 had a significantly shorter progression‐free survival ( P  = 0·00171) and overall survival (OS) ( P  < 0·001) than those without trisomy 21; additionally, patients with trisomy 21 in the rituximab‐treated cohort also had a significantly shorter OS ( P  = 0·000428). Multivariate analysis identified trisomy 21 as an independent risk factor in our cohorts with or without t(14;18) ( P  = 0·015). In conclusion, the presence of trisomy 21 was an independent risk factor for in FL. Chromosomal analysis of FL patients at diagnosis can provide useful information about their expected survival.